2013
DOI: 10.3906/tar-1208-58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-treatment with alkaline copper quat and copper azole on the mechanical properties of wood-based composites

Abstract: Two new triterpene glycosides, 3-ter (gazipashoside B, 2), were isolated together with 11 known compounds including 7 triterpene, 1 flavonoid, and 3 iridoidal metabolites from the aerial parts of Cephalaria gazipashensis (Dipsacaceae) . The structures of all compounds were elucidated by extensive evaluation of the spectroscopic data (1D-and 2D-NMR, HRESI-MS), as well as chemical examinations. The antimicrobial effects of all pure compounds were tested against gram-positive and gram-negative bacteria. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This association of occurrences suggests a probable harmful action of the active ingredients of the preservative product CCA-C on the mechanical performance of the plywood panel, as attributed by the Wood Handbook (IBACH, 2010) and by Acker and Stevens (1993), Vick and Kuster (1992) and Pinheiro (2001). This finding is contrary to that reported in the literature by Taşçioğlu et al (2014) and by Mendes et al (2013) who attributed the drop in properties to pressure treatment.…”
Section: Static Bendingcontrasting
confidence: 99%
See 1 more Smart Citation
“…This association of occurrences suggests a probable harmful action of the active ingredients of the preservative product CCA-C on the mechanical performance of the plywood panel, as attributed by the Wood Handbook (IBACH, 2010) and by Acker and Stevens (1993), Vick and Kuster (1992) and Pinheiro (2001). This finding is contrary to that reported in the literature by Taşçioğlu et al (2014) and by Mendes et al (2013) who attributed the drop in properties to pressure treatment.…”
Section: Static Bendingcontrasting
confidence: 99%
“…Despite the benefits of preservative treatment of wood and its by-products, the active ingredients of preservative products, such as chromium, copper and arsenic, react with wood during fixation, causing significant reductions in mechanical properties, especially if the drying processes are not controlled (TSOUMIS, 1991;VICK;KUSTER, 1992;ACKER;STEVENS, 1993, BARNES et al, 1996PINHEIRO, 2001;IBACH, 2010;MENDES et al, 2013;SEGUNDINHO et al, 2017). Other research suggests that the vacuum-pressure system and not the preservative itself would be the cause of the drop in physical-mechanical properties (TAŞÇIOĞLU; TSUNODA, 2010;MENDES et al, 2013;TAŞÇIOĞLU et al, 2014). The treatment of wooden panels would cause excessive swelling, in some cases irreversible, damaging the other properties.…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded that pretreatment with ACQ and CA within the investigated loading levels may not have detrimental effects on the physical and mechanical properties of bamboo OSB. In contrast, the post-treatment of vacuum-impregnation with ACQ (retentions: 0.65, 1.30, and 2.60 kg/m 3 ) and CA (0.25, 0.50, and 1.0 kg/m 3 ) was found to have negative effects on the MOE and MOR of OSB (Taşçioğlu 2013). Tascioglu and Tsunoda (2010a,b) also concluded that post-treatment with CA and ACQ was impractical for OSB because of the resulting high thickness swelling.…”
Section: Thickness Swellingmentioning
confidence: 78%
“…Because the solutions of waterborne ACQ and CA preservatives are normally low in concentration, an in-process treatment, which generally incorporates preservatives with dry wood elements before mat forming and hot-pressing, may result in very high mat moisture content, which in turn brings up challenges and difficulties for hot-pressing. Post-treatment with these preservatives often involves pressure impregnation and a subsequent drying process that causes excessive thickness swelling and thus has possible detrimental effects on both the structure and properties of OSB and other non-veneer wood composites (Tascioglu and Tsunoda 2010a, b;Taşçioğlu 2013). In contrast, with pretreatment, i.e., dipping or impregnating strands in dilute preservative solution, the treated strands can then be dried and used subsequently for OSB manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Wood-based composites can be protected by various methods including pre-treatment of particles, in-process treatment during manufacturing process, post-treatment after manufacturing of composites (Kirkpatrick andBarnes 2006, Taşçıoğlu 2013). The most practical way to protect composites could be post-treatment after manufacturing the composites by dipping, spraying, brushing or vacuum-pressure treatment (Taşçıoğlu 2013). Depending on the desired properties of cement-bonded wood composites, physical and mechanical properties can be improved with several factors such as cement-wood ratio, particle size and geometry, orientation of particles, treatment of particles or treatment composites with water repellent among other.…”
Section: Introductionmentioning
confidence: 99%